Resilience as a moderator of depression and anxiety: a bidimensional approach to predictors of subjective cognition in older adults. (2nd January 2023) - Miller, Luke R.; Divers, Ross; Reed, Christopher; Pugh, Erika; Calamia, Matthew
Abstract: Objectives: Subjective cognitive complaints (SCCs) have shown to be useful predictors of objective cognitive decline in older adults. Though psychopathology symptoms (e.g. depression, anxiety) have been linked to SCCs, little is known about the influence of positive psychology factors (e.g. resilience) on these complaints. The current study aimed to determine whether resilience predicts SCCs, and whether greater resilience moderates (or lessens) the effect of negative mental health symptoms on SCCs. Methods: Four hundred twenty-eight adults aged 60 years or older ( M  = 67.6, SD = 5.9) were recruited to participate in an online Qualtrics survey study. Surveys included assessed psychological resilience [University of Washington Resilience Scale 8-item short form (UWRS-8)], depression [Geriatric Depression Scale (GDS-15)], anxiety [Geriatric Anxiety Scale (GAS-30)], and SCCs [Perceived Deficits Questionnaire-Depression (PDQ-D); Barkley Deficits in Executive Functioning Scale-Short Form (BDEFS-SF)]. Results: Although greater resilience was only independently associated with less complaints on BDEFS total scores, resilience moderated (i.e. reduced) the negative effects of depression and anxiety on PDQ-D retrospective memory and planning subscales as well as BDEFS-SF total scores. Resilience also moderated (i.e. reduced) the negative effect of anxiety on PDQ-D total scores. Conclusion: With resilience lessening the effect of depression and anxiety on SCCS, our findings suggest positive psychological factors may be useful for understanding the prevalence of complaints. Future research should seek to replicate these findings and investigate relationships between additional positive psychological factors and cognitive health in old age including the use of both objective and subjective assessments of cognition.